Equações alométricas em plantios mistos visando à restauração da floresta estacional semidecidual - Ré, Danilo Scorzoni [UNESP]; Engel, Vera Lex [UNESP]; Ota, Liz Miyo Sousa [UNESP]; Jorge, Luiz Alberto Blanco [UNESP] (UFLA - Universidade Federal de Lavras, 2015)
Aiming to overcome the lack of knowledge about precise estimation of wood production potential of forest restoration systems, the objective of this study is modeling allometric relationships of nine tree species in alternative models of seasonal semideciduous forest restoration. The models fitted well to the data with satisfactory distribution of the residuals. The height-diameter relationship was best modeled by the Stoeffles model and the volume equations had the best fit with the Schumacher-Hall model, for many species. The equations obtained will be used in future studies of management and conservation of these plantations.

Visando a suprir a lacuna do conhecimento existente sobre a estimação precisa do potencial de produção madeireira de sistemas de restauração florestal, com o presente trabalho, objetivou-se modelar as relações alométricas (hipsométricas e volumétricas) de nove espécies comuns a modelos alternativos de restauração da floresta estacional semidecidual. Os modelos se ajustaram bem aos dados coletados e a análise de resíduos indicou distribuição satisfatória, tanto para os modelos hipsométricos como volumétricos. O modelo hipsométricos de Stoeffels e o modelo volumétrico de Schumacher-Hall foram os mais flexíveis, ajustando melhor para várias espécies. Essas equações obtidas serão usadas em futuros estudos de manejo e conservação de áreas em restauração.
Tree allometric equations in mixed forest plantations for the restoration of seasonal semideciduous forest
Keywords: Volume equations; Volumetric equations; Native species; Height-diameter relationships; Equações de volume; Equações hipsométricas; Espécies nativas; Relações altura-diâmetro